Effective stakeholder engagement for collation, analysis and expansion of antimicrobial resistance (AMR) data: a CAPTURA experience - Poudyal, Nimesh; Holm, Marianne; Joh, Hea Sun; Gautam, Sanjay; Sujan, Mohammad Julhas; Kwon, Soo Young; Sahikh, Affan; Shaw, Alina; Gallagher, Partick; Prifti, Kristi; Cho, Alyssa; Chi, Kyu-young Kevin; et al. (Clinical infectious diseases, 2023)
An effective implementation of antimicrobial resistance (AMR) surveillance projects requires sustainable and multidisciplinary engagement with stakeholders from various backgrounds, interests and aims. The “Capturing Data on Antimicrobial resistance Patterns and Trends in Use in Regions of Asia” (CAPTURA) project, funded by the Fleming Fund, initially targeted 12 countries in South Asia (SA) and Southeast Asia (SEA) to “expand the volume of historical and current data on AMR and antimicrobial usage” and support local agencies through capacity building activities.In this article, we focus on early stakeholder engagement activities and present overall statistics on AMR data collated from 72 laboratories across seven countries. This included 2.3 million records of antimicrobial susceptibility testing (AST) data, which were curated, analyzed, and shared back to the facilities for informed decision making.Approximately 98% of the data collated by CAPTURA originated from laboratories based in SA countries. Furthermore, country-wide data were analyzed to identify commonly reported pathogens in each country, followed by descriptions of AST practices and multidrug-resistant (MDR) pathogens. Overall, we found meager adherence to standard guidelines to perform and record AST results, and a significant number of MDR pathogens were reported.We conclude that close collaboration with the existing national mechanisms for identifying AMR data sources was crucial for the project's success. Although we show a vast retrospective dataset on AMR is available for data sharing in Asia, there remain critical gaps in data generation/management practice and analysis capacity for AMR data at most facilities.